IMPLEMENTING SUSTAINABLE ERGONOMICS FOR POWER-LOOM TEXTILE WORKERS - Kolgiri, Somnath; Hiremath, Rahul (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: This ergonomic study focuses on identifying and understanding the occupational health and safety risk aspects of power-loom industry workers from Solapur City, Maharashtra, India. Methods: The samples of 540 workers were assessed for their general physique, muscle tone (MT), a lung condition, and eyesight (ES) using different techniques. The body mass index (BMI) was used to asses normal physique. The Snellen chart was used to check normal eyesight. A peak flow meter was used to determine lung condition. Result: In this study, it was found that most of the workers were influenced by respiratory issues, increase in muscle tone, eye issues and musculoskeletal issues. The subjects were compared with controls. Linear regression analysis shows (OR: 0.356; 95% CI: 0.287–0.426) p<0.05*. Conclusion: Based on these outcomes; it strongly emphasized the need for policies for successful implementation of health safety program. Therefore, to improve the health of these workers the suggestions and recommendations were presented in accordance with the ergonomics principle and existing labor laws.